The Fatimids - Walker, Paul Ernest, 1941- (Leiden ; Boston)
vii, [1], 459 sayfa
Keywords: “The chapters of this volume contain a series of detailed studies of various aspects of Fatimid rule in the regions of its Mediterranean and Near Eastern empire, 909 to 1171 AD, including separately the role of the imam-caliph, wazīr, chief qāḍī and dāʿī, and other political and public offices of this Shīʿī caliphate. Geographically it covers North Africa, Sicily, the Levant, Hijaz, Cairo and Egypt in the medieval period, with special attention to books, science and libraries, court society, festivals, intellectual traditions and Ismaili doctrines, its religious appeal, military, enemies and rivals, among them the Abbasids, Umayyads, and Ibadis“--